Non-promulgation of mandatory COVID-19 vaccination in the Republic of Serbia - Radulović Srđan (Zbornik Radova Pravnog Fakulteta u Nišu, 2022)
The first COVID-19 case in the Republic of Serbia was registered on 6th March 2020. The World Health Organization declared the COVID-19 pandemic five days later. In the circumstances of the ongoing pandemic, the Republic of Serbia clearly faced, and is still facing, serious challenges. Once the infection began spreading, the state introduced various economic, legal, and medical measures to lessen the negative effects of the pandemic, constantly modifying them to adjust the rigidity of state response to the intensity of different waves of infection. Both individual and overall effects produced by the adopted measures are a highly interesting study topic. Yet, the available measures which were not introduced seem to be as interesting to research. This particularly refers to mandatory vaccination. In that con-text, two questions arise: what is the rationale for the authorities' decision not to introduce mandatory vaccination, and what it actually means from legal perspective. This paper focuses on the later question. Specifically, the paper aims to provide a possible interpretation of the recommended (non-mandatory) COVID-19 vaccination, and discuss the roles of participants and possible civil liability. In this pursuit, the author relies on the normative method and different analytical techniques, with due respect for theoretical achievements in medical law.